2014
DOI: 10.1136/jech-2014-204196
|View full text |Cite
|
Sign up to set email alerts
|

The recent economic recession and self-rated health in Estonia, Lithuania and Finland: a comparative cross-sectional study in 2004–2010

Abstract: Despite the rapid economic downturn, the short-term health effects in Estonia and Lithuania did not differ from those in Finland, although the recession years marked the end of the previous positive trend in self-rated health. The reduction in health disparities during the recession indicates that different socioeconomic groups were affected disproportionately; however, the reasons for this require further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 38 publications
6
33
2
3
Order By: Relevance
“…A 2001–2011 US study found a declining HRQoL in younger age groups, whereas the older age groups tended to report higher HRQoL 13. Similar trends have been observed in Estonia, Lithuania and Finland,14 and other studies found unexpected improvements of mentally oriented scales with increasing age 8 15. Various factors may cause such disparities between age groups in both HRQoL and its temporal trends.…”
Section: Discussionmentioning
confidence: 60%
“…A 2001–2011 US study found a declining HRQoL in younger age groups, whereas the older age groups tended to report higher HRQoL 13. Similar trends have been observed in Estonia, Lithuania and Finland,14 and other studies found unexpected improvements of mentally oriented scales with increasing age 8 15. Various factors may cause such disparities between age groups in both HRQoL and its temporal trends.…”
Section: Discussionmentioning
confidence: 60%
“…Multilevel studies also suggested that state-level unemployment as well as census-tract foreclosure risk was associated with declining SRH [26, 28, 29]. Results from most aggregate-level studies suggested a decline in SRH with the Great Recession, as well [25, 30]. The most rigorous aggregate-level study found a long-term decline in SRH after a possible brief period of improvement in the United Kingdom [30].…”
Section: Resultsmentioning
confidence: 99%
“…Despite great harmonisation efforts, we were not able to remove all differences between countries in data collection such as the framing of survey questions, the population coverage or the response rates. The tendency to report less-than-good SAH may differ between countries due to different cultural backgrounds,9 43 for example, persons in Central and Eastern European countries may tend to report their health as less good than persons in other European countries 44 45. However, as we focused on the trends in inequalities in SAH, we retained comparability over time within each country, and therefore consider the risk of bias due to between-country variations in these aspects to be limited.…”
Section: Discussionmentioning
confidence: 99%